Using toolkits to achieve STEM enterprise learning outcomes - Watts, Carys A; Wray, Katie (Education & training (London), 2012)
Purpose - The purpose of this paper is to evaluate the effectiveness of using several commercial tools in science, technology, engineering and maths (STEM) subjects for enterprise education at Newcastle University, UK.Design methodology approach - The paper provides an overview of existing toolkit use in higher education, before reviewing where and how tools are used across science and engineering disciplines. Feedback was collated from Newcastle educators and students to determine whether the projected enterprise learning outcomes were achieved. STEM learning outcomes were also mapped to the NCEE entrepreneurship learning outcomes framework.Findings - The paper investigated the use of three key enterprise toolkits across the Faculty of Science, Agriculture and Engineering and the Faculty of Medical Sciences, where the focus is on innovation and product service development, rather than on the desire to "be an entrepreneur". This reflection on practice evaluates the benefits and student perceptions of workshop tools for enterprise, decision making and teamwork. It makes comparison between the perceived employability needs of these students, and addresses the intended and actual outcomes of these tools.Research limitations implications - Evaluating toolkit use within a single university is constrained by common internal workings, however as exemplars of good practice this is of value to other UK higher education institutions.Practical implications - Consideration is given to entrepreneurial support and development, and whether using existing tools should be used for summative or for formative assessment. It also questions whether tools are fit for purpose.Originality value - This paper reveals patterns of tool use and their effectiveness across science and engineering.